FREQUENCY OF THE TRANSMISSIBLE VENEREAL TUMOUR IN DOGS: CASELOAD IN THE PATHOLOGY LABORATORY OF THE NATIONAL UNIVERSITY OF SAN MARCOS (PERIOD 1998-2004) - Mendoza V., Narda (2010)
The objective of this study was to determine the frequency of Transmissible Venereal Tumour (TVT) in dogs from Lima city, during 1998 to 2004, to establish the relationship with sex, breed, and age, and to determine the organs most affected by the tumours. The cytology and histopathology records of the Pathology Laboratory (School of Veterinary Medicine, Universidad Nacional Mayor de San Marcos) were analyzed. The frequency of TVT was 8.4% (78/925), and without sex effect. Crossbred dogs and dogs of one to five years of age were the most affected. The external genitalia were the most affected site (prepuce or penis in males and vulva or vagina in females). Extra genital lesions in the nasal, oral, and anal mucosa, skin, inguinal lymph nodules and spleen were also observed.